2021
DOI: 10.21037/apm-20-2382
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative pulmonary aspiration and regurgitation without aspiration in adults: a retrospective observational study of 166,491 anesthesia records

Abstract: Background: Pulmonary aspiration (PA) of gastric contents is a rare but serious perioperative complication. Recent studies focused on pediatric patients, but over a decade has passed since the latest incidence and outcome in adult population have been reported. Patients who experienced regurgitation without aspiration were rarely mentioned. Besides, our department proposed a modified rapid sequence induction (RSI) protocol in 2018 and its preventive effect remained to be examined.Methods: A total of 166,491 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 27 publications
1
27
1
Order By: Relevance
“…A recent retrospective record study in 155 830 adults evaluated the standard 2 hours of fasting for clear fluids and reported an incidence of regurgitation in elective anesthesia of 0.6 per 10 000 patients. 12 This incidence is lower than in our population and likely to be attributed to the retrospective study design. The authors noticed that some anesthesiologists considered regurgitation without aspiration relatively innocent and were inclined not to record this, leading to an underestimation.…”
Section: Regurgitationcontrasting
confidence: 61%
See 3 more Smart Citations
“…A recent retrospective record study in 155 830 adults evaluated the standard 2 hours of fasting for clear fluids and reported an incidence of regurgitation in elective anesthesia of 0.6 per 10 000 patients. 12 This incidence is lower than in our population and likely to be attributed to the retrospective study design. The authors noticed that some anesthesiologists considered regurgitation without aspiration relatively innocent and were inclined not to record this, leading to an underestimation.…”
Section: Regurgitationcontrasting
confidence: 61%
“…Although higher than anticipated, our current incidence of regurgitation matches the recent literature. 12,17 The German prospective multicenter observational (NIKS) study of 12 093 children evaluated the safety of a liberal fluid policy. 17 For children undergoing elective procedures after a fasting duration of 2.3 hours, the reported incidence of regurgitation was 32 per 10 000 patients, which is higher than in our study.…”
Section: Regurgitationmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the first public demonstration of general anesthesia with ether by William Thomas Morton Open Access *Correspondence: wolfgang.wetsch@uk-koeln.de in 1846, James Young Simpson reported the first death due to pulmonary aspiration during chloroform induced anesthesia in 1848 [4]. Today, anesthesiologists, critical care and emergency doctors take multiple precautions in order to prevent pulmonary aspiration when inducing general anesthesia, but regurgitation of gastric content can occur despite all precautions, as a review of 166,491 anesthesia records in a recent study showed: in 20 cases, they found pulmonary aspiration, and in an additional 20 cases there were signs of regurgitation without pulmonary aspiration [5]. Pulmonary aspiration can have varying clinical consequences -ranging from clinically none, to aspiration pneumonia due to bacteria transported into the lung alongside with the aspirate, [6] right up to severe acute respiratory distress syndrome (ARDS) with distinct hypoxemia -named "Mendelson Syndrome" after Curtis L. Mendelson, who described a case series of 66 healthy obstetrical patients with chemical pneumonitis after ether anesthesia [7].…”
Section: Introductionmentioning
confidence: 99%